Movement Patterns of Resident and Translocated Beavers at Multiple Spatiotemporal Scales in Desert Rivers - Doden, Emma; Budy, Phaedra; Avgar, Tal; Young, Julie K. (Frontiers in Conservation Science, 2022)
Wildlife translocations alter animal movement behavior, so identifying common movement patterns post-translocation will help set expectations about animal behavior in subsequent efforts. American and Eurasian beavers (Castor canadensis; Castor fiber) are frequently translocated for reintroductions, to mitigate human-wildlife conflict, and as an ecosystem restoration tool. However, little is known about movement behavior of translocated beavers post-release, especially in desert rivers with patchy and dynamic resources. We identified space-use patterns of beaver movement behavior after translocation. We translocated and monitored nuisance American beavers in desert river restoration sites on the Price and San Rafael Rivers, Utah, USA, and compared their space use to resident beavers after tracking both across 2 years. Resident adult (RA) beavers were detected at a mean maximum distance of 0.86 ± 0.21 river kilometers (km; ±1 SE), while resident subadult (RS) (11.00 ± 4.24 km), translocated adult (TA) (19.69 ± 3.76 km), and translocated subadult (TS) (21.09 ± 5.54 km) beavers were detected at substantially greater maximum distances. Based on coarse-scale movement models, translocated and RS beavers moved substantially farther from release sites and faster than RA beavers up to 6 months post-release. In contrast, fine-scale movement models using 5-min location intervals showed similar median distance traveled between RA and translocated beavers. Our findings suggest day-to-day activities, such as foraging and resting, were largely unaltered by translocation, but translocated beavers exhibited coarse-scale movement behavior most similar to dispersal by RSs. Coarse-scale movement rates decreased with time since release, suggesting that translocated beavers adjusted to the novel environment over time and eventually settled into a home range similar to RA beavers. Understanding translocated beaver movement behavior in response to a novel desert system can help future beaver-assisted restoration efforts to identify appropriate release sites and strategies.